Impact of ARTs on oncological outcomes in young breast cancer survivors. Issue 2 (8th December 2020) - Condorelli, M; De Vos, M; Lie Fong, S; Autin, C; Delvigne, A; Vanden Meerschaut, F; Wyns, C; Imbert, R; Cheruy, C; Bouziotis, J; de Azambuja, E; Delbaere, A; et al.
Abstract: STUDY QUESTION: What is the risk of recurrence in young breast cancer survivors who undergo ARTs following completion of anticancer treatment? SUMMARY ANSWER: ART in breast cancer survivors does not appear to have a negative impact on disease-free survival. WHAT IS KNOWN ALREADY: In healthy women, fertility treatment does not increase the risk of developing breast cancer. At the time of breast cancer diagnosis and before starting anticancer treatments, several studies have shown the safety of performing ART. However, the safety of ART in breast cancer survivors following completion of anticancer treatment remains under-investigated. In general, breast cancer survivors are counselled to avoid any hormonal treatment but there are limited data available on the effect of short exposure to high oestradiol levels during ART. The largest study in this regard included 25 breast cancer survivors exposed to ART and did not show a detrimental effect of ART on patient survival. Hence, taking into account that pregnancy after breast cancer does not affect cancer prognosis, defining the safety of ART in breast cancer survivors remains a priority. STUDY DESIGN, SIZE, DURATION: We conducted a retrospective multicentric matched cohort study including a cohort of breast cancer survivors who underwent ART (exposed patients) between January 2006 and December 2016. Exposed patients who were eligible for the study were matched according to known breast cancer prognostic factors. Matched breast cancer survivors did not undergo ART (non-exposed patients) and were disease-free for a minimum time that was not less than the time elapsed between breast cancer diagnosis and first ART for the matched ART-exposed patients. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data were retrieved from all survivors who had been diagnosed with breast cancer in eight participating centres at an age of ≤40 years, without metastasis, ongoing pregnancy, pre-existing neoplasia or ovarian failure. ART included ovarian stimulation for IVF/ICSI, clomiphene citrate treatment and hormone replacement therapy for embryo transfer. Data were collected from an oncological database for the selection of breast cancer patients in the non-exposed group. Exposed patients were matched (1:2) for germline BRCA status, tumour stage, anticancer treatment and age, whenever feasible. Matched groups were compared at baseline according to characteristics using conditional logistic regression. Kaplan–Meier curves were constructed to compare time to recurrence between groups, with the time of ART as starting point that has been adjusted in the non-exposed group. The analyses were performed using Stata IC/15.1. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 39 breast cancer patients in the ART group were eligible for the analysis and were matched with 73 controls. There was no statistical difference between the two groups for the presence of BRCA mutation, tumour characteristics, use of (neo)adjuvant chemotherapy and of adjuvant endocrine therapy. Exposed patients were younger than non-exposed patients (mean age 31.8 vs 34.3 years, respectively; P < 0.001). In the ART group, 89.7% were nulliparous at diagnosis compared to 46.6% of controls ( P < 0.001). ART was performed at a mean age of 37.1 years old, after a median time of 4.1 years following breast cancer diagnosis (range: 1.5–12.5). Median anti-Müllerian hormone at the time of ART was 0.28 ng/ml (range: 0–4.4) and median serum oestradiol peak level was 696.5 pg/ml (range: 139.7–4130). Median follow-up time from first attempt of ART was 4.6 years (range: 2.4–12.5) in the ART group. Adjusted follow-up time for the non-exposed group was 6.9 years (range: 1.1–16.5 years) ( P = 0.004). In the ART group, 59% of patients had a pregnancy after breast cancer compared to 26% in the non-exposed patients ( P = 0.001). Breast cancer relapsed in 7.7% versus 20.5% women in the ART and non-exposed groups, respectively (hazard ratio 0.46, 95% CI 0.13–1.62, P = 0.23). Median time to relapse was 1.3 (range: 0.3–2.7) years versus 4.5 (range: 0.4–11.1) years after ART and adjusted time in the ART and non-exposed groups, respectively ( P = 0.14). LIMITATIONS, REASONS FOR CAUTION: Although this is the first and largest multicentric study addressing the impact of ART on breast cancer recurrence to provide data on oestrogen exposure, only a small number of patients could be included. This reflects the reluctance of breast cancer survivors and/or oncologists to perform ART, and highlights the need for a prospective data registry to confirm the safety of this approach. This would offer the possibility for these patients, who are at a high risk of infertility, to fully benefit from ART. WIDER IMPLICATIONS OF THE FINDINGS: Although recent studies have proven that pregnancy after breast cancer has no detrimental impact on prognosis, counselling patients about the safety of ART remains challenging. Our study provides reassuring data on the use of ART in breast cancer survivors with favourable prognostic factors, for when natural conception fails. STUDY FUNDING/COMPETING INTEREST(S): M.C. and I.D. are funded by FNRS, Télévie-FNRS and Fonds Erasme. M.D.V. is a CooperSurgical scientific advisory board member and receives lecture fees for MSD, Gedeon-Richter and Ferring, outside the submitted work. M.L. has acted as a consultant for Roche and Novartis and has received honoraria from Theramex, Roche, Lilly, Pfizer, Novartis and Takeda, outside the submitted work. I.D. has acted as a consultant for ROCHE and has received speaker's fees from Novartis, outside the submitted work. E.d.A. has received honoraria and is a Roche/GNE, Novartis, SeaGen and Zodiac scientific advisory board member, has received travel grants from Roche/GNE and GSK/Novartis, and has received research grants from Roche/GNE, Astra-Zeneca, GSK/Novartis and Servier, outside the submitted work. A.D. is a recipient of a research grant from Ferring Pharmaceuticals and receives lecture and/or consultancy fees from Merck, Gedeon-Richter and Ferring Pharmaceuticals, outside the submitted work. The remaining authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.